A Note on Philology - ŠIMIĆ, Krešimir (Anafora, 2023)
The article analyzes the controversy between Ulrich von Wilamowitz-Möllendorff and Friedrich Nietzsche, which began after the publication of Nietzsche’s first book Die Geburt der Tragödie aus dem Geiste der Musik (1872), followed by the controversy between Walter Jackson Bate and Paul de Man on the occasion of the publication of Bate’s article The Crisis in English Studies (Harvard Magazine 85, 1982). With the help of the two polemics, the author outlines the basic guidelines in the nineteenth-century and twen- tieth-century understanding of philology. Finally, the article brings the author’s own view of philology from the point of view of Christian tradition, that is, the evangelical statement: καὶ ὁ λόγος σὰρξ ξγένετο (John 1,14).